Ai Khanoum: A Case Study into Material Culture as a Marker for Ethnocultural Identity and Syncretism on the Hellenistic Frontier - Richey-Lowe, David Thomas (Journal of Hellenistic Pottery and Material Culture, 2021)
The following paper focuses upon the Hellenistic site of Ai Khanoum in Afghanistan from an architectonic perspective and attempts to evaluate the degree to which the ethno-cultural identity of Graeco-Bactrian culture was subject to acculturation. An analysis of two case studies, namely the Temple with the Indented Niches (TIN) and the ›Herõon‹ of Kineas, reveals that, whilst the urban configuration and architectural designs can offer clues towards the diffusional relationship between local and Greek elements, one should be careful of relying too heavily on the supposition that a specific style of material culture equates to a set ethnic unit.